Articular eminence Inclination and its relationship with incisors mesiodistal inclination in skeletal class I occlusion adults with no clinical and radiographic symptoms of TMDs - Jahjah, Yazan; Hassan, Hazem (Latakia University Journal -Medical Sciences Series, 2015)
Articular eminence participates in the functional formation of the posterior guidance of the mandibular movement, it's the anatomical point where functional stresses can result in alteration of the contours of the articular eminence, and its inclination respectively, Hence, orthodontists need to know the relationship between the articular eminence Inclination and the mesiodistal inclination of upper and lower incisors to achieve more stable results of orthodontics treatment. Aim The aim of this research is to investigate the relationship of upper and lower incisors mesiodistal inclination with the inclination of the articular eminence in class I skeletal occlusion in adult subjects with no clinical nor radiographic symptoms of TMDs. Materials and methods: In result of radiographic study and a multistage clinical examination protocol, 46 Caucasian patients with no prior orthodontics treatment were selected (19 males, 27 females) from 16 to 27 years of age with skeletal class I occlusion and no clinical or radiographic signs and symptoms of TMDs. Furthermore, cephalometric evaluating of the Inclination of the articular eminence and the mesiodistal inclination of the incisors was performed; Pearson's Correlation Coefficient was calculated to investigate the relationship of articular eminence Inclination with the mesiodistal inclination of the incisors. Results: no significant relationship between incisors mesiodistal inclination and the articular eminence inclination was found. Conclusions the steepness of the articular eminence appears not to vary with mesiodistal inclination of the incisors in skeletal class I occlusion adults with no clinical and radiographic symptoms of TMDs. يشارك المنحدر المفصلي في التكوين الوظيفي للقيادة الخلفية لحركة الفك السفلي، إنه النقطة التشريحية حيث تستطيع الإجهادات الوظيفية أن تسبب تغيراً في حواف المنحدر المفصلي وبالتالي تغيراً في ميلانه أيضاً، ومن هنا تنبع أهمية التحقق من وجود علاقة بين ميلان المنحدر المفصلي من جهة وبين الميلان الأنسي الوحشي للقواطع العلوية والسفلية وذلك لتحقيق نتائج معالجة تقويمية أكثر استقراراً. هدف البحث: دراسة العلاقة بين ميلان المنحدر المفصلي من جهة وبين الميلان الأنسي الوحشي للقواطع العلوية والسفلية وذلك لدى بالغين ذوي إطباق صنف أول هيكلي وبدون أعراض سريرية ولا شعاعية لإضطرابات المفصل الفكي الصدغي. مواد وطرق البحث: من خلال الإستعانة بفحص الشعاعي وفحص سريري متعدد المراحل تم انتقاء 46 مريض من العرق قوقازي ممن لم يخضعوا لمعالجة تقويمية سابقة (19 ذكر و27 أنثى) تراوحت أعمارهم بين 16 و 27 سنة ذوي إطباق صنف أول هيكلي وبدون أعراض سريرية وشعاعية لإضطرابات المفصل الفكي الصدغي، حيث تم إجراء تقييم شعاعي سيفالومتري لميلان المنحدر المفصلي وللميلان الأنسي الوحشي لمحاور القواطع حيث تم لاحقاً إجراء تحليل معامل ارتباط بيرسون ما بين ميلان المنحدر المفصلي والميلان الأنسي الوحشي لمحاور القواطع. النتائج: لم نجد إرتباطاً ذو دلالة إحصائية ما بين ميلان المنحدر المفصلي وبين الميلان الأنسي الوحشي لمحاور القواطع. الخلاصة: لا يوجد إرتباط ما بين ميلان المنحدر المفصلي وبين الميلان الأنسي الوحشي لمحاور القواطع العلوية والسفلية لدى البالغين ذوي إطباق صنف أول هيكلي ليس لديهم أعراض سريرية وشعاعية لإضطرابات المفصل الفكي الصدغي.